2016
DOI: 10.1002/mrm.26282
|View full text |Cite
|
Sign up to set email alerts
|

Double‐gated myocardial ASL perfusion imaging is robust to heart rate variation

Abstract: Single-gated myocardial ASL suffers from reduced temporal SNR, while double-gated myocardial ASL provides consistent temporal SNR independent of HRV. Magn Reson Med 77:1975-1980, 2017. © 2016 International Society for Magnetic Resonance in Medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 35 publications
(57 reference statements)
3
30
0
Order By: Relevance
“…Global MP for diastolic SS‐EPI (1.67 ± 0.72 mL/g/min) and systolic SS‐EPI (1.50 ± 0.36 mL/g/min) were found to be statistically equivalent to diastolic bSSFP (1RR: 1.59 ± 0.80 mL/g/min) based on TOST with P ‐values of 0.022 and 0.031, respectively. MP values for diastolic SS‐EPI, systolic SS‐EPI and diastolic bSSFP were comparable to previous ASL‐CMR studies with diastolic 1RR bSSFP, but were slightly higher than previous positron emission tomography and first pass CMR studies. CMR first pass studies have shown that resting MP in systole and diastole should be equivalent.…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…Global MP for diastolic SS‐EPI (1.67 ± 0.72 mL/g/min) and systolic SS‐EPI (1.50 ± 0.36 mL/g/min) were found to be statistically equivalent to diastolic bSSFP (1RR: 1.59 ± 0.80 mL/g/min) based on TOST with P ‐values of 0.022 and 0.031, respectively. MP values for diastolic SS‐EPI, systolic SS‐EPI and diastolic bSSFP were comparable to previous ASL‐CMR studies with diastolic 1RR bSSFP, but were slightly higher than previous positron emission tomography and first pass CMR studies. CMR first pass studies have shown that resting MP in systole and diastole should be equivalent.…”
Section: Resultssupporting
confidence: 78%
“…This underestimation is a significant limitation of the FAIR technique. This effect was not detected in the data, likely because variation in MP observed between subjects is >30%, which is large but consistent with previous ASL‐CMR studies . Larger sample sizes will be required to detect differences on the order of <30% with existing ASL‐CMR techniques.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Trained networks were tested on 144 unseen ASL images acquired at rest and during adenosine stress from 6 heart transplant recipients. Training, validation, and testing data were drawn from previously published studies (31)(32)(33), where manual segmentation and quantitative reginal MBF from all subjects were readily available.…”
Section: Network Architecturementioning
confidence: 99%